Relationships between Scientific Process Skills and Scientific Creativity: Mediating Role of Nature of Science Knowledge - Gokhan Ozdemir; Ayhan Dikici (Journal of Education in Science, Environment and Health)
The purpose of this study is to explore the strength of relationships between 7th grade students’ Scientific Process Skills (SPS), Nature of Science (NOS) beliefs, and Scientific Creativity (SC) through Structural Equation Modeling (SEM). For this purpose, data were collected from 332 students of two public middle school students in Turkey. SPS, Nature of Scientific Knowledge Scale (NSKS) and SC instruments were used as data collection tools. Zero-order and partial correlation analysis, MANCOVA and ANCOVA analyses were conducted on the data. Two models were hypothesized. In Hypothesized Model 1, it was considered that SPS both directly and indirectly through subscales of NSKS predicted SC; whereas, in Hypothesized Model 2, it was considered that the SPS directly predicted SC. SEM analysis was conducted to test the two hypothesized models. Sobel’s z tests were conducted to examine the significance of the mediator roles of NSKS’s subscales in the relationships between SPS and SC. Results indicated that the relationships between SPS and SC were partially mediated by only the Testable subscale of NSKS; likewise, this relationship was partially mediated by second-order factor NSKS. Finally, we found that the Creative subscale of NSKS has a moderator role on predictive power of the SPS on the SC. Classroom implications obtained from the results are discussed in the paper.